Penafsiran Bernuansa Mu???tazili Dalam Tafsir Al-Kasyaf - Kerwanto; Unggul Purnomo Aji (At-Tahfidz: Jurnal Ilmu Al-Qur'an dan Tafsir, 2024)
Of the many tafsir books, Tafsir al-Kasyaf by al-Zamakhsyari is a book of tafsir that has a broad scope which is thought to have Mu'tazilah nuances in it. It was felt that previous studies had not yet optimally dissected the nuances of mutism in this book of tafsir, for this reason this research using the literature method was designed to explore this matter more deeply. The results of the research show that Tafsir al-Kasyaf is convincingly proven to have Mu'tazilah nuances by excluding one chapter, namely the Al-Qur'an is Kalamullah according to al-Zamakhsyari.